2019
DOI: 10.1017/s000711451800363x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition therapy for the management of cancer-related fatigue and quality of life: a systematic review and meta-analysis

Abstract: Cancer-related fatigue (CRF) is one of the most commonly reported disease- and treatment-related side effects that impede quality of life. This systematic review and meta-analysis describes the effects of nutrition therapy on CRF and quality of life in people with cancer and cancer survivors. Studies were identified from four electronic databases until September 2017. Eligibility criteria included randomised trials in cancer patients and survivors; any structured dietary intervention describing quantities, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 61 publications
0
56
0
1
Order By: Relevance
“…Also, a recent review of clinical trials that assessed nutritional interventions for preventing and treating CRF suggests that supplementation with probiotics but also ginseng, or ginger may improve cancer survivors' energy levels and that nutritional interventions, alone or in combination with other interventions should be considered as therapy for fatigue in cancer survivors. Nevertheless, there is lacking evidence to determine the optimal diet to improve CRF in cancer patients (262,273). Furthermore, also physical activity, psychosocial, mind-body, and pharmacological treatments have been proven to be effective (187).…”
Section: Nutrition Microbiome and Physical Activity And Its Associamentioning
confidence: 99%
“…Also, a recent review of clinical trials that assessed nutritional interventions for preventing and treating CRF suggests that supplementation with probiotics but also ginseng, or ginger may improve cancer survivors' energy levels and that nutritional interventions, alone or in combination with other interventions should be considered as therapy for fatigue in cancer survivors. Nevertheless, there is lacking evidence to determine the optimal diet to improve CRF in cancer patients (262,273). Furthermore, also physical activity, psychosocial, mind-body, and pharmacological treatments have been proven to be effective (187).…”
Section: Nutrition Microbiome and Physical Activity And Its Associamentioning
confidence: 99%
“…Earlier systematic analyses have indicated that exercise is an effective mean to improve CRF while evidences for nutritional supplements is not established [36]. A most recent meta-analysis including 15 intervention studies demonstrated nutrition therapy did not show definite effects on CRF and QoL in cancer patients [37]. Among these intervention trials, however, plant-based anti-inflammatory diets suggested possible benefits on CRF [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Despite links between nutrition and CRF, and multiple guidelines suggesting nutritional consultation as a possible treatment option for CRF [ 37 , 38 , 39 , 40 ], there are no evidence-based guidelines for the nutritional management of CRF. In addition, there are a limited number of nutrition-focused fatigue self-management programs that have been developed and tested [ 11 , 41 ]. To date nutritional interventions for the management of CRF have primarily focused on face-to-face or telephone-based nutritional counselling from a registered dietitian [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are a limited number of nutrition-focused fatigue self-management programs that have been developed and tested [ 11 , 41 ]. To date nutritional interventions for the management of CRF have primarily focused on face-to-face or telephone-based nutritional counselling from a registered dietitian [ 41 ]. Although nutritional counselling may be an effective method of providing individualized support [ 42 ], access to registered dietitians who have expertise in oncology may be limited [ 42 ], particularly within the context of a growing population of cancer survivors.…”
Section: Introductionmentioning
confidence: 99%